PENERAPAN MODEL PENGELOLAAN RADIO DBS FM SEBAGAI MEDIA PENINGKATAN PENGETAHUAN DAN PEMAHAMAN KEAGAMAAN MASYARAKAT - Imam Syafii; Hasanah Hasanah (Maddah : Jurnal Komunikasi dan Konseling Islam, 2020)
DBS FM Radio is a practicum radio for students majoring in communication and Islamic broadcasting (KPI) of the Da'wah Faculty of Ibrahimy University, Sukorejo, Situbondo. As a campus radio which is also known as student radio, college radio, university radio and student radio, the management system is very different from public radio or commercial radio. It becomes a big question when campus radio is managed by following the system applied by commercial radio. As a student practicum radio, it can actually trigger any problem in the form of shortages or difficulties of the announcer crew which ends with a failure to attract the interest or sympathy of listeners both internal listeners consisting of the students themselves and external listeners who come from the surrounding community. This study uses a qualitative method. with the results of research showing that the management of DBS FM radio as a campus radio can be identified a value system with a degree of effectiveness of management that is replicable and able to increase its role and function as a medium for enhancing and public knowledge